2002
DOI: 10.1051/0004-6361:20020305
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for weak MHD turbulence in the middle magnetosphere of Jupiter

Abstract: Abstract. In this paper we study the small scale-magnetic field fluctuations of the middle Jovian magnetosphere that are embedded in the strong background field B0 of Jupiter in the framework of turbulence theory. We perform a statistical analysis of these fluctuations using a five year set of Galileo spacecraft magnetic field data. Calculating power spectra of the fluctuations, we identify for the first time a spectral index of minus two for wave vectors perpendicular to B0. These results strongly support a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 43 publications
9
116
0
1
Order By: Relevance
“…the Jovian magnetosphere [148], where the parameter ζ L is much smaller than the unity over a broad range of length scales. Although as noted above the cascade will evolve in the direction of increasing ζ l for decreasing l, and may reach the strong turbulent regime on very small scales.…”
Section: Weak/intermediate Turbulencementioning
confidence: 99%
“…the Jovian magnetosphere [148], where the parameter ζ L is much smaller than the unity over a broad range of length scales. Although as noted above the cascade will evolve in the direction of increasing ζ l for decreasing l, and may reach the strong turbulent regime on very small scales.…”
Section: Weak/intermediate Turbulencementioning
confidence: 99%
“…However, it has been demonstrated both analytically and numerically that the energy cascade occurs predominantly in the plane perpendicular to the guiding magnetic field [8,10,15,16], which ensures that even if the turbulence is weak at large scales, it encounters the strong regime as the cascade proceeds to smaller scales. Although weak turbulence may exist in some astrophysical systems (see, e.g., [13,[17][18][19]), magnetic turbulence in nature is typically strong, in which case an exact analytic treatment is not available. In this case, high-resolution, well-optimized numerical simulations play a significant role in guiding our understanding of the turbulent dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation as to why we did not observe fluctuations on the timescale of one minute or so, even though Saur et al (2002) did see them in the magnetosphere, could be that the three pixels to estimate seeing effects. As in Figure 4, the large negative velocities seen between pixels 122 and 132 are due to uneven illumination across the slit as it crosses the dawn limb of the planet.…”
Section: Resultsmentioning
confidence: 70%
“…Our study is the first attempt to detect velocity fluctuations in the Jovian system to look for this augmented Joule heating. (Saur et al, 2002) found that fluctuations were typically present in all of the Galileo data they examined, and thus a persistent feature of the Jovian magnetosphere. Their analysis was sensitive to timescales between 24 s and 4500 s at a distance of 26 R J from the planet, at which distance they estimated Alfvén travel times in the magnetosphere to be 375 s per Jovian radius (1 R J =71 492 km).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation